Importance of extended blood group genotyping in multiply transfused patients. Issue 3 (June 2017) - Osman, Nadila Haryani; Sathar, Jameela; Leong, Chooi Fun; Zulkifli, Noor Fadzilah; Raja Sabudin, Raja Zahratul Azma; Othman, Ainoon; Ahmad Asnawi, Asral Wirda
Abstract: Blood group antigen systems are not limited to the ABO blood groups. There is increasing interest in the detection of extended blood group systems on the red cell surface. The conventional method used to determine extended blood group antigens or red cell phenotype is by serological testing, which is based on the detection of visible haemagglutination or the presence of haemolysis. However, this technique has many limitations due to recent exposure to donor red cell, certain drugs or medications or other diseases that may alter the red cell membrane. We aimed to determine the red cell blood group genotype by SNP real time PCR and to compare the results with the conventional serological methods in multiply transfused patients. Sixty-three patients participated in this study whose peripheral blood was collected and blood group phenotype was determined by serological tube method while the genotype was performed using TaqMan ® Single Nucleotide Polymorphism (SNP) RT-PCR assays for RHEe, RHCc, Kidd and Duffy blood group systems. Discrepancies were found between the phenotype and genotype results for all blood groups tested. Accurate red blood cell antigen profiling is important for patients requiring multiple transfusions. The SNP RT-PCR platform is a reliable alternative to the conventional method.